2020
DOI: 10.21203/rs.3.rs-125991/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 and the Risk of Dementia: A Population-Based Study

Abstract: IntroductionHerpes Simplex Virus 1 (HSV1) is a neuroinvasive virus capable of entering the brain which makes it a candidate pathogen for increasing risk of dementia. Previous studies are inconsistent in their findings regarding the link between HSV1 and dementia, therefore, we investigated how HSV1 relates to cognitive decline and dementia risk using data from a population-based study. MethodsWe measured HSV1 immunoglobulin (IgG) antibodies in serum collected between 2002 and 2005 from participants of the Rott… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…The study conducted by Murphy et al in 2021 supports the null hypothesis as they found no association between HSV-1 seropositivity and risk of dementia and Alzheimer's disease (with an adjusted hazard ratio of 1.18, 95% CI 0.83; 1.68) and hence concluded that HSV-1 does not associate with dementia incident in the general population. [40].…”
Section: Other Possible Resultsmentioning
confidence: 99%
“…The study conducted by Murphy et al in 2021 supports the null hypothesis as they found no association between HSV-1 seropositivity and risk of dementia and Alzheimer's disease (with an adjusted hazard ratio of 1.18, 95% CI 0.83; 1.68) and hence concluded that HSV-1 does not associate with dementia incident in the general population. [40].…”
Section: Other Possible Resultsmentioning
confidence: 99%
“…For instance, HSV-1 IgG seropositivity has been associated with an 18-fold increased odds of memory deficits in middleaged adults (Dickerson et al, 2008). Associations between HSV-1 IgG seropositivity and impaired cognition were also reported in other groups, e.g., healthy soldiers (Fruchter et al, 2015), young individuals (Tarter et al, 2014;Vanyukov et al, 2018) and older adults (Zhao et al, 2020;Murphy et al, 2021). Therefore, the clinical biomarker of HSV-1 exposure (i.e., IgG seropositivity) is likely to be linked to impaired memory and other cognitive measures, while biomarkers of HSV-1 reactivation or productive infection (i.e., high IgG levels or IgM seropositivity) is linked to AD (Letenneur et al, 2008;Lovheim et al, 2015a;Warren-Gash et al, 2019).…”
Section: Memory Impairmentmentioning
confidence: 85%
“…One key limitation of these studies is that HSV-1 seropositivity indicates the history of prior HSV-1 exposure. Seropositivity alone does not inform the status of HSV-1 infection; that is, active or latent infection, or viral replication in the central or peripheral nervous systems or peripheral epithelial cells (Dickerson et al, 2008;Murphy et al, 2021). Therefore, the possible link of causality or pathophysiological pathways between HSV-1 seropositivity and memory impairment remains unclear (Vanyukov et al, 2018).…”
Section: Lip Infectionmentioning
confidence: 99%
“…Herpes simplex virus type 1 (HSV-1), a neuroinvasive virus, has been linked to moderate cognitive impairment in recent population-based studies (Murphy et al, 2021) and has also been associated with the development and poor prognosis of AD in patients with comorbidity (Itzhaki et al, 1997;. While not conclusive evidence, HSV-1 DNA has been found to colocalize with Aβ plaques in human AD brains (Wozniak et al, 2009) and promote Aβ accumulation in neurons (Wozniak et al, 2007).…”
Section: Herpes Simplex Virus Type 1 Dysregulation Of Cofilinmentioning
confidence: 99%
“…When HSV-1 infects a host cell, actin dynamics are manipulated via LIMK and SSH1 regulation of cofilin during the viral lifecycle (Zheng et al, 2016). HSV-1 alone causes cofilin dysregulation with subsequent memory and cognitive defects (Zheng et al, 2016;Murphy et al, 2021). Coupled with AD, HSV-1 exacerbates this deteriorating cognitive ability .…”
Section: Herpes Simplex Virus Type 1 Dysregulation Of Cofilinmentioning
confidence: 99%